Soil Subsidence on Peat Land Due to Rainfall; Case Study of Pundu Region, Central Kalimantan - Enny Rahayu; Idum Satia Santi; Chandra Riski Alfikri Harahap (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
This study aims to determine the extent to which rainfall affects soil subsidence on peatlands in PT. BGA. TBk., Pundu, Central Kalimantan. The research was conducted at Katari Estate, PT BGA, Tbk. Pundu Central Kalimantan in September - December 2019. The research method used is the survey method, which consists of two stages, namely the preliminary survey and the main survey. A preliminary survey was conducted to determine the research location while the main survey was carried out to obtain research data, namely monthly rainfall data and subdidence in 2014 – 2018. To see the relationship between rainfall and land subsidence, Linear and Polynomial Regressions were made at lag 1, lag 2, and lag 3. Regression with lag 1 is the relationship between rainfall last year with land subsidence this year and rainfall last month with land subsidence on peatlands this month in the same year, and so on for lag 2 and lag 3. The results show that the regression between The best rainfall with soil subsidence on peatlands is the annual Lag 1 Linear Regression. This means that last year's rainfall has an effect on this year's subsidence. with the equation, Y = - 0.004 X + 1.209, where R² = 0.582. This equation is obtained from the correlation between X (average rainfall) from 2015-2018 and Y is soil subsidence also from 2015-2018. While the regression between last month's rainfall and this month's land subsidence in each year (2015 – 2018), shows a low correlation.